Donaldson type invariants for algebraic surfaces : transition of moduli stacks - 望月, 拓郎 (Lecture Notes in Mathematics, 2009)
This text defines and studies an algebro-geometric analogue of Donaldson invariants by using moduli spaces of semistable sheaves with arbitrary ranks on a polarized surface. The goal is to obtain a weaker version of the relations among the invariants.